A Review of Evaluating Hematopoietic Stem Cells Derived from Umbilical Cord Blood's Expansion and Homing - Islami, Maryam; Soleimanifar, Fatemeh (Current Stem Cell Research & Therapy, 2020)
Transplantation of hematopoietic stem cells (HSCs) derived from umbilical cord blood (UCB) has been taken into account as a therapeutic approach in patients with hematologic malignancies. Unfortunately, there are limitations concerning HSC transplantation (HSCT), including (a) low contents of UCB-HSCs in a single unit of UCB and (b) defects in UCB-HSC homing to their niche. Therefore, delays are observed in hematopoietic and immunologic recovery and homing. Among numerous strategies proposed, ex vivo expansion of UCB-HSCs to enhance UCB-HSC dose without any differentiation into mature cells is known as an efficient procedure that is able to alter clinical treatments through adjusting transplantation-related results and making them available. Accordingly, culture type, cytokine combinations, O2 level, co-culture with mesenchymal stromal cells (MSCs), as well as gene manipulation of UCB-HSCs can have effects on their expansion and growth. Besides, defects in homing can be resolved by exposing UCB-HSCs to compounds aimed at improving homing. Fucosylation of HSCs before expansion, CXCR4-SDF-1 axis partnership and homing gene involvement are among strategies that all depend on efficiency, reasonable costs, and confirmation of clinical trials. In general, the present study reviewed factors improving the expansion and homing of UCB-HSCs aimed at advancing hematopoietic recovery and expansion in clinical applications and future directions.
Keywords: expansion